Physcion effectively mitigates ovariectomy-induced osteoporosis in mice - Yun-Ho Hwang; Su-Jin Kim; Sung-Ho Kim; Sung-Tae Yee (Elsevier, 2020)
Aims: In this study, an ovariectomized mouse model was used to investigate the therapeutic effect of physcion on bone loss caused by estrogen deficiency. Material and methods: After ovariectomy (OVX), animals were allocated to 5 groups, that is, SHAM, OVX (OVX + vehicle), E2 (OVX + β-estradiol, 0.03 μg/head/day), Phy 2 (OVX + physcion 2 mg/kg/day), and Phy 8 (OVX + physcion 8mg/kg/day) groups. Estradiol and physcion were administered for six weeks from day 4 post-OVX, and various factors related to bone loss were measured. Key findings: We found physcion significantly reduced estrogen deficiency-induced increases in body weight and bone turnover markers (calcium, inorganic phosphoric acid, alkaline phosphatase, total cholesterol), and that it inhibited reductions in bone mass and bone mineral density (BMD) by inhibiting osteoclast activity. Significance: These results suggest that physcion is a good candidate for preventing or treating osteoporosis in postmenopausal women.